MiR-153-5p promotes sensibility of colorectal cancer cells to oxaliplatin via targeting Bcl-2-mediated autophagy pathway. Issue 8 (2nd August 2020) - He, Yong; Zhang, Ling; Tan, Fei; Wang, Li-Fang; Liu, De-Hui; Wang, Rong-Juan; Yin, Xiong-Zhang
ABSTRACT: Oxaliplatin (L-OHP) is one of the effective chemotherapeutic drugs for colorectal cancer (CRC). Further investigation into the molecular mechanism of chemoresistance could improve outcomes for patients with colorectal cancer. Recently, microRNAs have been reported as a key in drug resistance of tumors. In this study, we aimed to investigate the effects of miR-153-5p in L-OHP-resistant CRC cells, and its underlying mechanism. Downregulation of miR-153-5p was observed in CRC cells, while upregulation of miR-153-5p enhances the chemosensitivity of CRC/L-OHP cells. The autophagy of CRC/L-OHP cells was markedly increased after exposure to L-OHP but abolished by the upregulation of miR-153-5p. Dual-luciferase reporter assays validated that Bcl-2 was a direct target of miR-153-5p. In conclusion, our data suggested that miR-153-5p was a mediator of cisplatin resistance in colorectal cancer by affecting Bcl-2-mediated autophagy, indicating a new therapeutic target for CRC treatment. GRAPHICAL ABSTRACT: uf0001 MiR-153-5p was a mediator of cisplatin resistance in colorectal cancer by affecting Bcl-2-mediated autophagy